Precautionary credit lines: A means to contain contagion in financial markets? - Stefan M. Golder (Institut für Weltwirtschaft (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1999)
The liberalization of capital accounts and the integration of financial markets in recent years have helped to spur growth in many emerging markets and have allowed global investors to diversify risks internationally. Furthermore, increased capita! mobility has helped to tame governments in their fiscal and monetary policies. Nevertheless, the Asian currency and financial crisis and its aftermath have revealed structural problems on the national as well as on the international level and have imposed significant costs on emerging markets as well as on the world economy. Triggered by these developments, a broad international consensus has emerged to support reforms to strengthen the international financial system. The aim of these reforms will be to create an international financial system that captures the benefits of open and integrated financial markets, and at the same time minimizes the risk of financial crises to emerge and spread to other countries. While the former refers to the need for greater transparency, accountability and prudential regulation, the latter is concerned with the improvement of existing and the creation of new mechanisms for the prevention and resolution of financial crises. International institutions such as the IMF can contribute to the stability of the international financial system. A prominent proposal initially raised by the Clinton administration in fall 1998 designs the creation of a new crisis facility of the IMF to prevent contagion in financial markets. On its recent meeting of April 23, the IMF's Executive Board agreed to provide Contingent Credit Lines for its member countries. The goal of such a facility is to provide preventive credit lines to countries whose economies are fundamentally sound, but which are threatened by financial market contagion and which may lose access to capital markets. In the absence of contagion, these countries should therefore be able to rely on a sustained flow of capital from abroad. The new facility gives rise to a number of questions. First, the distinction between countries in need of ex ante policy adjustments and countries that follow sound economic policies, i.e., the eligibility for the new facility, must be resolved in advance. Second, projections about the likely financial requirements of such a facility and the consequences for the Fund's liquidity position are needed. Another issue relates to the question whether and how private and bilateral creditors should be involved in this new facility. Finally, there is a need for clear guidelines about the terms and conditions that would apply to this new facility. However, as shown in the paper, it will prove difficult to fulfill these criteria and to avoid additional problems related to a precautionary credit line. Based on this skeptical judgment, the paper explores a number of alternative means to foster the stability of the international financial system through a better involvement of private sector creditors. This could be achieved through the introduction of option-type mechanisms that would allow debtors to trigger liquidity support in the case of a crisis. A more radical approach would involve limits to creditors in cases when they would like to reduce their short-term exposure. Another avenue would comprise a reorganization of private claims, either by modifying bond contracts or by adapting bankruptcy procedures. The main task for policy makers, however, remains to increase transparency and improve supervision in financial markets and to pursue sound economic policies.
Keywords: 330; Internationaler Kredit; Internationales Währungssystem; Devisenspekulation; Internationaler Preiszusammenhang; Moral Hazard; Verursacherprinzip; Bankenaufsicht; International; Welt; Finanzmarktkrise